Influence of age on adjustment of readmitted teenage mothers in secondary schools kenya: a case study of Ugenya sub-county - Opondo, Christine Mwajuma; Raburu, Pamela A.; Aloka, Peter J. O. (International Journal of Current Research, 2017)
Teenage motherhood is a worldwide problem with 36.4 million girls giving birth before the age of 18 years in developing Countries and Kenya is no exception. The current study investigated the difference in adjustment of readmitted teenage mothers in select age. Mixed method research approach was used and within it Sequential Explanatory Design was adopted. The target population consisted of 288 respondents namely 23 principals, 23 guidance and counseling teachers and 242 counties. The findings of the study indicated that the older readmitted teenage mothers had higher mean score in overall adjustment than the younger ones. For example, whereas the teenage mothers aged group of above 19 years had a mean of 2.63 (SD=.316, SE=.056), those who were age below 15 years only had a mean adjustment of 1.72 (SD=.244, SE=.031). It was clearly shown that there was a statistically significant difference in overall adj =144.5, p<05 It was therefore concluded that there was significant influence of age on adjustment, with older readmitted teenage mothers adjusting better than their younger counterparts. Findings reported indicated that most young teen mothers had a lot of difficulties in adjusting to school life on return to school. However, the older and more mature teenage mothers adjusted appropriately and easily cope with the problems after counselling. It means that the age of teenage mothers influenced adjustment. However, it was reported that, the younger teenage mothers easily shared their problems with the counsellors in school but had challenges in adjusting to school. The study recommends that teacher counsellors should utilize relevant cognitive and behavioral therapy techniques to help young teenage mothers adjust appropriately at school.
Keywords: Age; Adjustment; Re-admitted teenage mothers; secondary schools; Ugenya; Kenya